Translating Finnish Pedagogical Excellence into Sustainable School Management: Strategies for Fostering Equity and Diversity in Primary Education - Muchammad Tholchah; Devi Prasad Bhattarai (Al Kautsar: Knowledge Advancements in Teaching Strategies and Research, 2026)
This study aims to analyze strategies for translating Finnish pedagogical excellence into sustainable primary school management, focusing on fostering equity and diversity. This evaluation urgently required as many traditional school management models as possible in centralized systems to struggle to balance rigorous academic standards with student well-being and inclusive practices. The novelty of this research lies in the development of a "Contextual Translation" framework that mediates progressive Finnish values with local institutional constraints. Employing a qualitative approach with a single-case study design at a private elementary school in Indonesia, the research involved eight key informants, including the principal, curriculum coordinator, and senior teachers. Primary data were gathered through virtual interviews via Zoom, participant observations conducted through high-resolution video recordings of learning activities, and an in-depth analysis of strategic documents from 2024–2025 to ensure the credibility of remote qualitative procedures. The results indicate that the implementation of Phenomenon-Based Learning (PhenoBL) effectively fosters student agency and intrinsic motivation, evidenced by a 30% increase in student-led project initiatives. The success of this transformation is supported by a distributive leadership model that disperses authority among teachers, creating organizational resilience. However, adaptation faces challenges such as institutional rigidity and heavy administrative burdens. The study finds that "Digital Literacy" is a critical hurdle; without it, graduates and teachers cannot navigate the digitalized tools necessary for modern interdisciplinary learning. The study recommends the adoption of social justice leadership and the most urgent step: establishing an Industrial Advisory Board or a localized "Innovation Committee" to cut through bureaucratic hurdles by integrating local values like gotong royong.